Critical heat flux of highly subcooled water flow boiling in circular tubes with and without internal twisted tapes under high mass fluxes. (April 2016) - Yan, Jianguo; Bi, Qincheng; Zhu, Ge; Cai, Laizhong; Yuan, Qizheng; Lv, Haicai
Highlights: Critical heat flux of highly subcooled water flow boiling was investigated experimentally under high mass fluxes. A twisted tape was inserted to induce swirl flow, and its effect on CHF enhancement was focused. A number of subcooled CHF correlations were assessed for both smooth tubes and twisted-tape tubes. A modified correlation of Arment et al. was proposed to predict the swirl-flow subcooled CHF. Abstract: This study focuses on the critical heat flux (CHF) of highly subcooled water flow boiling under high mass fluxes, particularly with respect to the thermal–hydraulics analysis in fusion reactor components. The experiments were performed in vertical circular tubes those were uniformly heated by a large AC power supply. Twisted tape was employed to induce swirl flow in order to further enhance the subcooled CHF. This study obtained several high CHF data points in both smooth tubes and twisted-tape tubes, which can enhance relevant high-CHF databases. The influences of thermodynamic quality, mass flux, pressure, and twisted tape on subcooled CHF were discussed. The results show that twisted tapes can allow significant increase in subcooled CHF under high mass fluxes. The CHF enhancement effect is more obvious when using twisted tapes with smaller twist ratios. Available existing subcooled CHF correlations were compared with the experimental data from the present and others' studies for both smooth tubes and twisted-tape tubes. For smooth tubes, the CHF look-up table has satisfactory prediction accuracy. For twisted-tape tubes, a modified correlation of Arment et al. was proposed to predict the swirl-flow subcooled CHF.